Malaysia, Singapore & Brunei - Richmond, Simon; Harper, Damian; Parkinson, Tom; Rawlings-Way, Charles; Watkins, Richard (Lonely Planet Publications Pty Ltd., 2007)
This travel guide to Malaysia, Singapore and Brunei provides information for visitors of all budgets, including advice on getting there, accommodation, local cuisine, places to visit, language tips, and health and safety.